Anodic Deposition of Enantiopure Hexahelicene Layers. Issue 15 (18th May 2018) - Vacek, Jan; Hrbáč, Jan; Strašák, Tomáš; Církva, Vladimír; Sýkora, Jan; Fekete, Ladislav; Pokorný, Jan; Bulíř, Jiří; Hromadová, Magdalena; Crassous, Jeanne; Storch, Jan
Abstract: Helicenes are polyaromatic compounds with chiral properties useful for many applications in optoelectronics, separation processes, chiral recognition and catalysis. Here we focused on the electrochemistry of carbo[ n ]helicenes ( n =5, 6, 7). The cyclic voltammograms of racemic mixtures of target compounds in acetonitrile/0.1 M tetrabutylammonium perchlorate at a glassy carbon electrode reveal the diffusion‐controlled reactions in both anodic and cathodic potential regions. Electrochemical behaviors are different for individual helicenes, [7]helicene undergoes redox transformation easily in comparison to the other investigated compounds, which is in agreement with DFT (density functional theory) calculations. Generally, the multi‐component anodic process of helicenes is observable at potentials from +1.5 to +2.5 V, leading to the formation of deposited structures (layers) on the electrode surface. The helicenes were electrodeposited onto transparent indium tin oxide (ITO) electrodes and characterized by atomic force microscopy, UV/Vis, Raman spectroscopy and ellipsometry. Finally, the anodic deposition of P and M enantiomers of [6]helicene was performed using ITO substrates, resulting in the formation of enantiopure layers of nanometer thicknesses, as confirmed by circular dichroism spectroscopy. The discovered electrosynthetic procedure opens up a new possibility for the immobilization of chiral helicene layers onto solid supports. Abstract : The long and winding road : the electrochemical behavior, electronic properties and spectral characterization of carbo[ n ]helicenes ( n =5, 6, 7) are reported. Focusing on the anodic electrodeposition of helicene layers, the comparative study opens up a new possibility for the immobilization of chiral helicene layers onto solid supports.